Electrolyte abnormalities in asphyxiated newborns - D., Satheesh Kumar; M., Thenmozhi; ., Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: Perinatal asphyxia is the most common cause of neonatal morbidity and mortality in worldwide. It accounts for 23% of all neonatal deaths. Electrolyte abnormalities are more common in the immediate post asphyxiated period and influence neonatal the outcome effectively. Aim of this study was to measure the serum sodium, potassium and calcium levels in immediate postnatal period of asphyxiated newborns and assess the correlation with different degree of birth asphyxia. Methods: The serum sodium, potassium and calcium levels were measured in asphyxiated newborns in the early post-natal period. Both intramural and extramural newborns were included irrespective of their mode of delivery but according to the Apgar score. The measured electrolyte values were compared with the different severity of asphyxia. Results: Out of 100 newborns 53 had hyponatremia, 10 had hyperkalemia and 3 had hypocalcemia. The serum sodium and potassium levels showed significant P value (<0.00) with the different degree of both asphyxia but calcium levels were not significant (p valve = 0.06). There was a negative linear correlation with sodium and calcium levels and positive correlation with the serum potassium levels. Conclusions: Hyponatremia was significant in all stages of birth asphyxia, hyperkalemia was significant with increased severity of birth asphyxia and hypocalcemia was only weakly significant even in severe birth asphyxia.